Turkey’s National Interest in The Civil War in Libya for The Period 2019-2020 - Mohammad Naufal Eprillian Salsabil (Budapest International Research and Critics University, 2022)
The Civil War that took place in Libya in 2011, where the uprising carried out by the Libyan people against the regime of Muammar Khadafi and triggered by a series of events in the Middle East or better known as the